Link between Parkinson’s disease and melanoma: insights into the influence of the PARK gene family - Wu, Jinghua; Xiong, Haojun; Chen, Jinhua; Yang, Dengrong; Li, Yujing; Wang, Jinglai; Chen, Jiaoyu; Zhang, Ruixia; Zhang, Ruiqi; Li, Xiwei; Li, Feng; Zhang, Runnan; et al. (Frontiers in Oncology, 2025)
Parkinson’s disease (PD) is a common neurodegenerative disorder characterized by damage to dopaminergic neurons within the substantia nigra region of the midbrain. Melanoma, on the other hand, is a malignant skin tumor formed by the abnormal proliferation of melanocytes, often linked to genetic predisposition and ultraviolet exposure. Emerging evidence confirms a significant association between PD and melanoma, with individuals afflicted with PD displaying a higher susceptibility to melanoma development. The PARK family genes, known for their involvement in PD etiology, emerge as key players in elucidating this intricate relationship. Through a comprehensive review, it becomes evident that different PARK gene mutations exert varied impacts on both PD and melanoma pathogenesis. For instance, mutations in PARK1/4 influence α-synuclein aggregation in both PD and melanoma, while PARK8 mutations modulate autophagy pathways in both PD and melanoma. The roles of PARK2 and PARK13 in melanoma warrant further investigation. Additionally, PARK6 mutations influence mitophagy mechanisms in PD and melanoma, with implications regarding melanoma proliferation through the PI3K/AKT pathway. Therefore, delineating the precise contributions of PARK genes to PD and melanoma pathophysiology holds paramount importance in devising therapeutic strategies for both PD and melanoma.